Implementation of The Concept of Collaborative Collection Development in The Governance of Student Contributed Books - Saputra, Andi (Edulib, 2024)
Books donated by students have made a significant contribution to the development of collections at the Andalas University Library because they are used as a graduation requirement. This study aims to develop the concept of collaborative collection development (CCD), namely collaborative partnerships by implementing a coordinated purchasing system in the management of student-donated books. Collaboration is carried out by establishing partnerships with external parties (publishers/bookstores). The research method used is to develop and evaluate system performance. Data collection was carried out through observation and interviews with related parties. The results showed that the coordinated purchasing system was able to overcome duplication problems and increase the uniqueness and heterogeneity, as well as the quality of student-donated books. In order for the coordinated purchasing system to provide maximum results, the library must collaborate with several partners. So that the uniqueness of the collection can be increased and the problem of duplication can really be resolved properly.